Analysis of Students’ Understanding of Adapted Topic using The WhatsApp Group (WAG), Learning Video, and Assisted Module - Merisa, Desy; Sujana, Atep; Sopandi, Wahyu (International Conference on Elementary Education, 2021)
This study aims to determine the extent of students' understanding of online learning by using instructional videos and WAG-assisted modules. The method used in this study is a pre-experimental method with one group pretest-posttest design. The research subjects were sixth-grade students in a public school in Bandung who were selected by purposive sampling technique. The data analysis used in this research is descriptive quantitative. The instrument used to explore the conceptual understanding was a test with two tiers of 20 questions. The first level questions are in the form of multiple choices with four choices to determine the answer, while the second level questions ask for reasons for choosing the answers on the first level. The research findings show that after implementing online learning using instructional videos and modules, students' understanding has increased quite significantly as indicated by the n-gain value from the low category to the high category. Analysis of the level of understanding of students shows changes towards the better at each level.